1991
DOI: 10.1007/bf00172735
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of catechin and its metabolites by Bradyrhizobium japonicum

Abstract: Catechin, a condensed tannin was utilized as sole carbon source by Bradyrhizobium japonicum. Protocatechuic acid, phloroglucinolcarboxylic acid, phloroglucinol, resorcinol and hydroxyquinol were identified as intermediates of catechin degradation. The aromatic substrates favoured good growth up to 5 or 10 mM. B. japonicum tolerated up to 50 mM catechin and phloroglucinolcarboxylic acid, 40 mM phloroglucinol and resorcinol, 30 mM protocatechuic acid and 10 mM hydroxyquinol. Catechin-induced cells oxidized catec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Cell‐free enzyme extracts were prepared by ultrasonication as described earlier 16. All samples and the controls were analyzed in triplicate.…”
Section: Methodssupporting
confidence: 92%
“…Cell‐free enzyme extracts were prepared by ultrasonication as described earlier 16. All samples and the controls were analyzed in triplicate.…”
Section: Methodssupporting
confidence: 92%
“…However, catechin and oxalate co-incubation studies show that the oxalate has no direct effect on the chemical structure or stability of (±)-catechin (data not shown). It is possible that the presence of L. sericeus in the field attracts microbial communities that degrade catechin, and in fact it has been shown that Bradyrhizobium japonicus can utilize catechin as a sole carbon source (Hopper and Mahadevan 1997). …”
Section: Oxalate May Influence Plant Interactions In Natural Ecosystemsmentioning
confidence: 98%
“…The pathways for flavonoid biodegradation in a number of bacterial species have been proposed and partially characterized, although the enzymes and intermediates have not been satisfactorily elucidated (Barz, 1970;Pillai & Swarup, 2002;Rao & Cooper, 1994Rao et al, 1991;Arunachalam et al, 2003;Hopper & Mahadevan, 1997;Schoefer et al, 2003;Winter et al, 1989;Braune et al, 2001;Jeffrey et al, 1972). Rhizobium leguminosarum bv.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, common intermediate molecules were observed in the degradation of several flavonoids by aerobic bacteria. For example, phloroglucinol and protocatechuic acid originated from quercetin (Rao et al, 1991;Rao & Cooper, 1994) and catechin (Arunachalam et al, 2003;Hopper & Mahadevan, 1997) after C-ring cleavage. Additionally, 3,4-dihydroxyphenylacetic acid and 3-(4-hydroxyphenyl)propionic acid, as well as phloroglucinol, were detected in the degradation of other flavonoids by anaerobic bacteria (Winter et al, 1989;Schoefer et al, 2003;Braune et al, 2001;Schneider & Blaut, 2000).…”
Section: Introductionmentioning
confidence: 99%